«CONSTITUIONAL AND LEGAL FOUNDATIONS ELECTRAL SYSTEM OF THE KYRGYZ REPUBLIC» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this article, the author analyzes the factors determining the relevance of theelectoral law and the process on the basis of historical data. Reveals the essence of the problem ofsuffrage, which for citizens should not be a profit. This is a civic duty and it is necessary to increasethe spiritual value of this right. Some possible ways of reforming the electoral sphere are revealed,through training and ways of introducing a new look at the electoral right of a citizen. The conclusion of the article is the need to develop a curriculum for grades 10-11 to improve consciousnessand literacy in electoral law and the process.
Keywords: Constitution, electoral system; process; law; elections; falsification; bribery; civic duty; position.